(untitled) (Research, Society and Development, 2021)
The article approaches education and the achievement of anti-racist policies as capable of identifying the arbitrary cultural value of the model of imposition and inculcation by education, according to public policies to combat racism. The methodology used is a literature review on anti-racist policies in Education, when observing the context of Latin America, using the paradigms of adopting multiculturalism and transversality. Therefore, it presents the reception of multiculturalist policies in the region, as well as how these are welcomed by the education systems of Latin America. It presents the proposal for its achievement and consolidation of the diversity model; opportunity in which the various governments in the region adopted transversality policies. In this way these anti-racist public policies, in defending the proposal of inclusion, in the policy cycle, by multiculturalism through transversality, is the reason why the assessment agencies are unable to demonstrate how this integration would improve the State’s assessment criteria. Therefore, it does not produce social effectiveness.